Conceptualising Transformative Praxis - Luitel, Bal Chandra; Dahal, Niroj (Journal of Transformative Praxis, 2020)
Transformative praxis covers a wide range of scholarly pursuits for social change via reflexive research and practice. Praxis is used to raise the consciousness of researchers, participants and social actors through a constant embracing of a critical stance toward text, discourse, and the lifeworld. A host of images are used to conceptualise the notion of transformative praxis as epistemology, theory, methodology, professional development, genres and logics, and empowerment. Transformative praxis as epistemology refers to multiple ways of knowing embedded in critiquing, reconceptualizing self, and envisioning; whereas transformative praxis as theory is informed by the critical scholarship of strengths and limitations of theories, philosophies, and perspectives as a means for social change. Our ideas of transformative praxis as methodology are embedded in the commitments of researchers and practitioners to engage in the process of holistic meaning making. Reflexive engagement of researchers and practitioners in the lifeworld contributes to the conceptualisation of transformative praxis as professional development. Transformative praxis as empowerment draws upon the ongoing discourse of an emancipatory interest that emphasises autonomy, responsibility, and criticality. The articles in this issue focus on developing cosmologically responsible educational processes, deviance as pedagogical action, holistic learning, and pedagogical change through multiparadigmatic research processes.